1992
DOI: 10.1016/0021-9975(92)90015-m
|View full text |Cite
|
Sign up to set email alerts
|

Feline non-suppurative meningoencephalomyelitis. A clinical and pathological study

Abstract: A spontaneous neurological disease in cats characterized by behavioural and motor disturbances was investigated by clinical, morphological and immunological methods. Neuropathological examination showed a marked inflammatory reaction in the cerebral leptomeninges and the grey matter of the brain. In the white matter, the reaction was moderate. The changes consisted of perivascular cuffing by mononuclear cells and neuronal damage. The brain stem (thalamus, mesencephalon, caudal colliculus) was most severely aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
82
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 10 publications
14
82
1
Order By: Relevance
“…Epidemiological studies have documented that diverse species of warm-blooded animals including cats possess circulating antibodies to BDV. In cats, a spontaneous non-suppurative meningoencephalomyelitis with clinical signs of ataxia and behavioral abnormalities, referred to as staggering disease (SD), is thought to be a counterpart of Borna-encephalitis, because the prevalence of BDV-specific antibodies seen in these cats is higher than that seen in randomly selected domestic cats, not having neurological disorders [18,20,22,23,28,30,31,34]. Moreover, a feline BDV has been isolated from the central nervous system of cats with SD [24].…”
mentioning
confidence: 99%
“…Epidemiological studies have documented that diverse species of warm-blooded animals including cats possess circulating antibodies to BDV. In cats, a spontaneous non-suppurative meningoencephalomyelitis with clinical signs of ataxia and behavioral abnormalities, referred to as staggering disease (SD), is thought to be a counterpart of Borna-encephalitis, because the prevalence of BDV-specific antibodies seen in these cats is higher than that seen in randomly selected domestic cats, not having neurological disorders [18,20,22,23,28,30,31,34]. Moreover, a feline BDV has been isolated from the central nervous system of cats with SD [24].…”
mentioning
confidence: 99%
“…In domestic cats, an characteristic disease of the central nervous system has been observed in Sweden [9]; the dominating clinical sign is an unsteady (staggering) gait. Histopathological examination of the cats showed that the inflammatory reaction of the central nervous system was most pronounced in the grey matter of the brain stem, basal ganglia and hippocampus.…”
mentioning
confidence: 99%
“…Other clinical signs reported in cats with 'staggering disease' that have not been observed in any of the cats described in our study include tremors, seizures, inability to retract the claws, pruritus, fever and constipation. 13,14 Behavioural changes commonly occur in cats with forebrain disease and have been reported in both diseases. The type of histological lesions is consistent with lymphohistiocytic meningoencephalomyelitis in cats with 'staggering' disease, as well as in the cats included in our study; however, the distribution of the infiltrates in the CNS is not entirely the same.…”
Section: Discussionmentioning
confidence: 99%